Pengaruh Kepemimpinan, Kompetensi, dan Lingkungan Kerja terhadap Peningkatan Produktivitas Karyawan pada PT Rascar Auto Sport Palembang - Ananda Putri, Raisa; Mohammad Kurniawan DP; Yeni (Jurnal Bisnis Islam dan Kewirausahaan, 2025)
This study aims to analyze the impact of leadership, competence, and work environment on the productivity of employees of PT Rascar Auto Sport Palembang. This type of research is quantitative descriptive. The technique of determining the number of samples used saturated sampling with a total of 90 respondents. Data analysis used data quality test, classical assumption test, and multiple linear regression analysis with t-test (partial), F test (simultaneous), and R test. The results of the study show that leadership has a positive and significant effect on the productivity of PT Rascar Auto Sport Palembang employees. Competence has a positive and significant effect on the productivity of PT Rascar Auto Sport Palembang employees. The work environment does not have a positive and significant effect on the productivity of PT Rascar Auto Sport Palembang employees. Leadership, competence and work environment simultaneously have a positive and significant effect on the productivity of PT Rascar Auto Sport Palembang employees. The correlation value results for the variables Leadership, Competence, and work environment related to employee productivity (Y) were positive